A Descriptive Study on Literary Translation in the Context of Eco-Translatology - Nesibe Erkalan Çakır (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The eco-translatology approach, in which the translator is at the center of the translation process and, accordingly, has the responsibility for the ecology of the target text, has recently become a topic of interest to researchers. In the eco-translation approach, the translation process not only highlights the ecological elements in the source text but also creates ecological awareness for the reader of the target text. The ecotranslatology approach was put forward by Chinese translation studies researchers Gengshen Hu and Youlan Tao to examine the act of translation from an ecological perspective. Therefore, this approach brings ecological elements to the forefront in the translation process and in this respect differs from other translation approaches. Therefore, this approach can be said to interpret translation in light of eco-holism, unlike various fields such as linguistics, literature, culture, communications, or art. The study aims to interpret literary translation in the context of the eco-translatology approach. In this context, I have first identified the simile expressions in Yashar Kemal’s book, Yılanı Öldürseler and I compared these simile expressions with their French translations in light of the eco-translatology approach. For the analysis, I’ve taken into account the following fundamental four principles Hu and Tao (2016) proposed within the framework of their approach: the principle of balance and harmony, the principle of multiple eco-integration, the principle of symbiosis and diversity, and the principle of translator responsibility. As a result of the analysis, the simile expressions in the source text are observed to have mostly been translated into French in accordance with the principles of eco-translatology.